SURVEY KETERAMPILAN PASSING BAWAH BOLA VOLLY DI EKSTRAKURIKULER SMPN 6 MUARA UYA - Muhamad Adi Pratama; Perdinanto; Akhmad Amirudin (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2024)
Underpassing is a basic skill that must be mastered in order to be able to play volleyball by receiving the ball from the serve and then passing to a teammate to attack. This research aims to determine the skills in passing under volleyball of extracurricular students at SMPN 6 Muara Uya. The method used is quantitative descriptive. The population used in this research was extracurricular volleyball students at SMPN 6 Muara Uya, totaling 15 male students. Basically, total sampling technique was used for this research. This research uses data collection techniques using a Volleyball Skill Test Passing test. The results of the data obtained from research on the level of volleyball underpassing skills of extracurricular students at SMPN 6 Muara Uya are generally in the